2017
DOI: 10.1128/jb.00001-17
|View full text |Cite
|
Sign up to set email alerts
|

DdaR (PA1196) Regulates Expression of Dimethylarginine Dimethylaminohydrolase for the Metabolism of Methylarginines in Pseudomonas aeruginosa PAO1

Abstract: Dimethylarginine dimethylaminohydrolases (DDAHs) catalyze the hydrolysis of methylarginines to yield L-citrulline and methylamines as products. DDAHs and their central roles in methylarginine metabolism have been characterized for eukaryotic cells. While DDAHs are known to exist in some bacteria, including Streptomyces coelicolor and Pseudomonas aeruginosa, the physiological importance and genetic regulation of bacterial DDAHs remain poorly understood. To provide some insight into bacterial methylarginine meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Taken together, the present results showed that RpoN directly regulates QS and T6SS by directly binding to promoters of lasI, rhlI, rhlA, rhlR, pqsA, pqsH, pqsR, hcpA, and hcpB. Previous studies show that RpoN affects the expression of nitrogenregulated genes (glnK-amtB, nirBD, nasA, nasST, and nosRZDFYL) (16) and interacts with EBPs to regulate diverse metabolic pathways, including glycine catabolism, (R)-3hydroxybutyrate catabolism, ethanolamine metabolism, methylarginine metabolism, flagellum biosynthesis, dicarboxylate transport, aromatic amino acid catabolism, and acetoin catabolism (24)(25)(26)(27)(28)(29) (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, the present results showed that RpoN directly regulates QS and T6SS by directly binding to promoters of lasI, rhlI, rhlA, rhlR, pqsA, pqsH, pqsR, hcpA, and hcpB. Previous studies show that RpoN affects the expression of nitrogenregulated genes (glnK-amtB, nirBD, nasA, nasST, and nosRZDFYL) (16) and interacts with EBPs to regulate diverse metabolic pathways, including glycine catabolism, (R)-3hydroxybutyrate catabolism, ethanolamine metabolism, methylarginine metabolism, flagellum biosynthesis, dicarboxylate transport, aromatic amino acid catabolism, and acetoin catabolism (24)(25)(26)(27)(28)(29) (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…The potential regulatory pathways and interplays of RpoN are proposed according to our observations and previous studies. RpoN affects the expression of nitrogen-regulated genes (glnK-amtB, nirBD, nasA, nasST, and nosRZDFYL) (16) and regulates dicarboxylates transport, amino acid catabolism, ethanolamine catabolism, (R)-3-hydroxybutyrate, methylarginines, and acetoin catabolism (24)(25)(26)(27)(28)(29). The typical QS systems, including the las, rhl, and pqs systems and their interactions, were summarized based on previous reports (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa PAO1 can convert methylarginines resulting in l -citrulline and methylamines by use of dimethylarginine dimethylaminohydrolases, coded by ddaH gene, which is induced in the presence of the substrate …”
Section: Introductionmentioning
confidence: 99%
“…Different stress-related signals regulate these EBPs through their N-terminal regulatory domains [ 39 ]. Two EBPs, DdaR and MifR, interact with the σ 54 factor to induce the transcription of dimethylarginine dimethylaminohydrolase and PA5530 genes by sensing aromatic amino acids and extracellular C 5 -dicarboxylates, respectively [ 40 , 41 ]. In addition, the σ 54 factor regulates the glyoxylate pathway, ethanolamine catabolism, ( R )-3-hydroxybutyrate, the glycine cleavage system, and pyocyanin biosynthesis via EatR, HbcR, and GcsR, respectively [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%